Insights Into Timing, Risk Factors, and Outcomes of Stroke and Transient Ischemic Attack After Transcatheter Aortic Valve Replacement in the PARTNER Trial (Placement of Aortic Transcatheter Valves). (September 2016) - Kapadia, Samir; Agarwal, Shikhar; Miller, D. Craig; Webb, John G.; Mack, Michael; Ellis, Stephen; Herrmann, Howard C.; Pichard, Augusto D.; Tuzcu, E. Murat; Svensson, Lars G.; Smith, Craig R.; Rajeswaran, Jeevanantham; et al.
Abstract : Background—: Prior studies of stroke and transient ischemic attack (TIA) after transcatheter aortic valve replacement (TAVR) are limited by reporting and follow-up variability. This is a comprehensive analysis of time-related incidence, risk factors, and outcomes of these events. Methods and Results—: From April 2007 to February 2012, 2621 patients, aged 84±7.2 years, underwent transfemoral (TF; 1521) or transapical (TA; 1100) TAVR in the PARTNER trial (Placement of Aortic Transcatheter Valves; as-treated), including the continued access registry. Stroke and TIA were identified by protocol and adjudicated by a Clinical Events Committee. Within 30 days of TAVR, 87 (3.3%) patients experienced a stroke (TF 58 [3.8%]; TA 29 [2.7%]; P =0.09), 85% within 1 week. Instantaneous stroke risk peaked on day 2, then fell to a low prolonged risk of 0.8% by 1 to 2 weeks. Within 30 days, 13 (0.50%) patients experienced a TIA (TF 10 [0.67%]; TA 3 [0.27%]; P >0.17). Stroke and TIA were associated with lower 1-year survival than expected (TF 47% after stroke versus 82%, and 64% after TIA versus 83%; TA 53% after stroke versus 80%, and 64% after TIA versus 83%). Risk factors for early stroke after TA-TAVR included more postdilatations, pure aortic stenosis without regurgitation, and possibly more pacing runs, earlier date of procedure, and no dual antiplatelet therapy; high pre-TAVR aortic peak gradient was a risk factor for stroke early after TF-TAVR. Conclusions—: Risk of stroke or TIA is highest early after TAVR and is associated with increased 1-year mortality. Modifications of TAVR, emboli-prevention devices, and better intraprocedural pharmacological protection may mitigate this risk. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00530894. Abstract : Supplemental Digital Content is available in the text.